Nanocaged platforms: modification, drug delivery and nanotoxicity. Opening synthetic cages to release the tiger. Issue 4 (9th January 2017) - Sahandi Zangabad, Parham; Karimi, Mahdi; Mehdizadeh, Fatemeh; Malekzad, Hedieh; Ghasemi, Alireza; Bahrami, Sajad; Zare, Hossein; Moghoofei, Mohsen; Hekmatmanesh, Amin; Hamblin, Michael R.
Abstract : Nanocages are a type of high-capacity drug-carrier for multi-modality medical treatments and theranostics, with high functionalization and targeted/stimuli-responsive delivery capabilities. Abstract : Nanocages (NCs) have emerged as a new class of drug-carriers, with a wide range of possibilities in multi-modality medical treatments and theranostics. Nanocages can overcome such limitations as high toxicity caused by anti-cancer chemotherapy or by the nanocarrier itself, due to their unique characteristics. These properties consist of: (1) a high loading-capacity (spacious interior); (2) a porous structure (analogous to openings between the bars of the cage); (3) enabling smart release (a key to unlock the cage); and (4) a low likelihood of unfavorable immune responses (the outside of the cage is safe). In this review, we cover different classes of NC structures such as virus-like particles (VLPs), protein NCs, DNA NCs, supramolecular nanosystems, hybrid metal–organic NCs, gold NCs, carbon-based NCs and silica NCs. Moreover, NC-assisted drug delivery including modification methods, drug immobilization, active targeting, and stimulus-responsive release mechanisms are discussed, highlighting the advantages, disadvantages and challenges. Finally, translation of NCs into clinical applications, and an up-to-date assessment of the nanotoxicology considerations of NCs are presented.